Correction to 'Phylogenetic evidence for a shift in the mode of mammalian body size evolution at the Cretaceous–Palaeogene boundary', and a note on fitting macroevolutionary models to comparative paleontological data sets. Issue 7 (26th May 2014) - Slater, Graham J.; Freckleton, Robert
Summary In this note, I correct two errors from an earlier paper that investigated tempo and mode of mammalian body size evolution across the Cretaceous‐Palaeogene boundary. Both errors arose from use of branch length rescaling under the Ornstein‐Uhlenbeck process, which I here show to be inappropriate for non‐ultrametric trees. Correction of these errors does not change the conclusions of my original study. However, recognition of the underlying problem highlights that comparative methods developed by biologists for examining trait evolution on ultrametric trees may not always be appropriate for paleontological datasets.